2023
DOI: 10.3390/molecules28093716
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Naringin for Use against Bone and Cartilage Disorders

Abstract: Bone and cartilage disorders are the leading causes of musculoskeletal disability. There is no absolute cure for all bone and cartilage disorders. The exploration of natural compounds for the potential therapeutic use against bone and cartilage disorders is proving promising. Among these natural chemicals, naringin, a flavanone glycoside, is a potential candidate due to its multifaceted pharmacological activities in bone and cartilage tissues. Emerging studies indicate that naringin may promote osteogenic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 143 publications
1
5
0
Order By: Relevance
“…A total of 2911 OP-related DEGs then underwent enrichment analyses using KEGG and GO. KEGG analysis revealed that OP-related DEGs were mainly enriched in the PI3K/Akt and Wnt signaling pathways, which was consistent with numerous studies reporting a role for the PI3K/Akt and Wnt signaling in osteogenic differentiation 23 , 24 . GO function analysis showed that OP-related DEGs were mainly enriched in response to oxidative stress, ROS, and H 2 O 2 in BP and were mainly enriched in binding growth factor receptors, peroxisome proliferator-activated receptors, and NO synthase in MF.…”
Section: Discussionsupporting
confidence: 89%
“…A total of 2911 OP-related DEGs then underwent enrichment analyses using KEGG and GO. KEGG analysis revealed that OP-related DEGs were mainly enriched in the PI3K/Akt and Wnt signaling pathways, which was consistent with numerous studies reporting a role for the PI3K/Akt and Wnt signaling in osteogenic differentiation 23 , 24 . GO function analysis showed that OP-related DEGs were mainly enriched in response to oxidative stress, ROS, and H 2 O 2 in BP and were mainly enriched in binding growth factor receptors, peroxisome proliferator-activated receptors, and NO synthase in MF.…”
Section: Discussionsupporting
confidence: 89%
“…Chrysin is the main active ingredient extracted from the purple wisteria plant and the Chinese red pine, both belonging to the family of Fabaceae , while naringenin is a secondary metabolite of citrus plants of Rutaceae ( 37 ). Both compounds have been confirmed to possess various biological activities, such as antioxidant ( 38 ), anti-inflammatory ( 39 ), anti-cancer ( 40 ), anti-asthmatic, anti-bacterial ( 41 ), and anti-arthritis effects ( 42 ), and they can enhance the host innate immune response ( 43 ). In recent years, domestic and foreign studies have found that chrysin and naringenin have good inhibitory effects on DNA and RNA viruses, including enterovirus 71, hepatitis virus, influenza virus, and dengue virus, providing theoretical references for the development of new antiviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Although NG was extensively developed as an anti-inflammatory and osteogenesis drug in previous studies, there are fewer reports on its osteo-immunomodulation properties. [59][60][61] In this study, the influence of the NG released from NG-MBG/PLLA scaffolds on the osteogenic differentiation, inflammation reaction, and immune regulation of mBMSCs, RAW264.7, and macrophage-conditioned cultured mBMSCs was fully investigated. Moreover, the slow release of NG can be achieved by loading NG on MBG, which also avoids the cytotoxicity caused by excessive drug concentration.…”
Section: Osteogenic Differentiation Of Mbmscs In the Macrophage-condi...mentioning
confidence: 99%